Queer correctives: discursive Neo-homophobia, sexuality, and Christianity in Singapore - Pak, Vincent (Advances in sociolinguistics, 2025)
"This book explores Christian discourses of sex and sexuality in Singapore to argue that metanoia, the theological concept of spiritual transformation, can be read as a form of neo-homophobia that coaxes change in the queer individual. Drawing on Foucauldian critical theory and approaches in discourse studies, it shows how language is at the centre of this particular iteration of neo-homophobia, one that no longer finds value in overt expressions of hate and disdain for those with non-normative sexualities, but relies extensively on seemingly neutral calls for change and transformation in personal lives"-- Provided by publisher